-2/3-1=5/6

Simple and best practice solution for -2/3-1=5/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2/3-1=5/6 equation:


-2/3-1 = 5/6

-1-2/3 = 5/6

-(2/3+1) = 5/6

-5/3 = 5/6

L <> R

See similar equations:

| 85+7m=1955 | | w^2+3W+2.25=8 | | -29.95-5.50x= | | 12x^2+43x+15=0 | | k=400(-8.15) | | 6x+6=2x-4 | | 7D=105 | | 6(x-4)-19=23-(x+5) | | 4x-5b=4c | | 8x^2+7=5x^2+4 | | 4x+27=3x+0 | | -3-4(2d-3)=4 | | (-3.2)(-8.61)=f | | Y/2=56 | | -2x=-4ab | | a/8=4/3 | | e=(8.002)(0.4) | | 4N=200 | | W/6=96 | | 4(2x-12)=40 | | X*2-7x+10=0 | | 8v+10=150 | | 2/3x=71/3 | | (-21.04)(-4.2)=d | | x/6=7/2 | | 0=2.5y-20 | | (1+2i)(1+3i)= | | (1+2i)(1+3i)= | | 5(2x+8)-3(3x-5)=4x-2 | | x+6/x-6=0 | | c=10(-15.82) | | 7x+5y=175 |

Equations solver categories